Covariance Based approach SEM with Bollen-Stine Estimation (Case Study Analysis of The Effect of Teacher and Principal Competence on Achievement of National Standards) - Kasmuri Kasmuri; I Made Tirta; Yuliani Setia Dewi (Jurnal ILMU DASAR, 2015)
Applications of covariance Based SEM (CB-SEM) generally use the maximum likelihood, based upon the assumption on the normal distribution of data. One alternative that could be applied if the data were not normally distributed is estimation using  Bollen-Stine bootstrap approach. In this study, the method is applied to reveal the influence of teacher competence, the principal competence, to the value of achievement of national education standards in secondary schools in Banyuwangi.The objective of this paper was to determine and analyze the relationship and to know the  the most dominant indicators of  measure latent variables between the  the principal, teachers competences on national standards of educational attainment in secondary schools in Banyuwangi. The results  indicate that all of the indicator of variables are  valid and reliable to measure corresponding latent variables. Each latent variable has the most dominan indicator. For the principal competence  latent variables the most dominant  indicator is the entrepreneurial competence, for teachers competency the most dominant is personal competence, whereas for  national education standards, the most dominant  standard of facilities. Principal competence  has indirect influence on national education standard achievement, but directly affect the competence of teachers.  Teacher competence directly influence national education standards.Keywords: Power Competence Teachers, Competence Principal, National Education Standards,  covariance Based SEM, Bollen-Stine Bootstrap Estimates